Interpretasi Validitas dan Reliabilitas Instrumen Kemampuan Berpikir Aljabar - Nubatonis, Ofirenty Elyada; Jupri, Al; Mulyaning A, Endang Cahya (Department of Mathematics, Universitas Negeri Gorontalo, 2024)
This research aims to interpret the validity and reliability of the items on the algebraic thinking ability instrument which are linked to content, context, question structure and students' cognitive level. The development of the algebraic thinking ability instrument was carried out in four stages by adapting the Plomp development model. The first stage (initial assessment), conducting a theoretical study of algebraic thinking abilities and curriculum analysis. The second stage (design), draft questions by paying attention to the relationship between indicators of algebraic thinking ability and learning objectives. Furthermore, this question design was validated by three experts in the field of mathematics education. The fourth stage (realization/construction) is testing the instrument which includes testing validity, reliability, distinguishability and level of difficulty. Apart from that, in the fourth stage the test results are also interpreted, evaluated and revised. The instrument was tested on 19 class VII students at one of the junior high schools in Bandung City. Interpretations of validity, reliability, distinguishability and level of difficulty are related to content, context, question structure and students' cognitive level. The results of the analysis at this stage are used as a reference for improving the instrument. The instrument produced in this research is a description question consisting of four items that are valid and reliable and can be used to measure algebraic thinking abilities, especially those related to generalization, transformation and metaglobal abilities.